Molecular and Anti-oxidant Effects of Wheat Germ Oil on CCl4-Induced Renal Injury in Mice - Haidan Mostafa El-Shorbagy (Journal of Applied Pharmaceutical Science, 2017)
The protective effect of wheat germ oil (WGO) as a natural antioxidant was evaluated against carbon tetrachloride (CCl4)-induced nephrotoxicity, genotoxicity and alterations in gene expression in mice kidney. WGO group: received olive oil orally for 2 days then WGO orally for 8 days, CCl4 group: received CCl4 orally for 2 days then olive oil for 8 days, CCl4 + WGO group: received CCl4 for 2 days then WGO for 8 days. Administration of CCl4 induced different abnormal patterns in P53 exons (5,6,7and 8), altered the histological architecture of kidney tissues, down-regulated mRNA expression of Bcl-2gene, and reduced the PCEs/NCEs ratio, the efficiency of kidney function and the concentrations of some antioxidant enzymes. On the other hand, it increased the number of micronucleus, % DNA fragmentation and mRNA expression of BAX gene causing apoptosis that has been proven by DNA ladder assay. Supplementation of WGO has ameliorated these effects of CCl4 through markedly improving different measured parameters, suggesting that WGO effectively protects kidney against CCl4-induced oxidative damage in mice. The nephroprotective and free radical scavenging effects of WGO might be due to the presence of bioactive constituents that could be useful against toxic effects of hazardous agents like CCl4.
Keywords: Wheat germ oil,Carbon tetrachloride,Oxidative stress,DNA fragmentation,Micronucleus,kidney.